Finance et risque aux États-Unis : vers une nouvelle frontière ? - Christine Zumello (Revue LISA)
This article raises the question of the evaluation and anticipation of risk on financial markets in the United States. The various types of risk are analysed as well as the main methods used to measure risk. The subprime crisis which dominated the end of the second G.W. Bush presidential term seemed to bring the whole financial and economic system to the brink of collapse. The central notion of the measure and control of risk hinges on the role of the political sphere versus the financial sphere.